2017
DOI: 10.1002/slct.201700287
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and Scintillation Modulation Upon UV/X‐ray‐Induced Photochromism in Europium Tungstate Phosphors

Abstract: Rare earth (RE) tungstates with general formula REW2O6(OH)3 (RE = YIII or EuIII) were synthesized by hydrothermal method by using different citric acid contents. The prepared samples exhibit both UV and X‐ray‐induced photochromism at room temperature, as well as photomodulated luminescence. The presence of citric acid residues improves the photochromism when the samples are UV‐irradiated, but has a secondary effect when the material is exposed to X‐ray, evidencing particular mechanisms of action in each case. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 73 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Ionizing radiations, especially X-ray radiation from natural and artificial sources, pose a variety of potential health risks if inappropriately used, which has aroused extensive attention from our society. As such, the precise detection of X-ray radiation is highly desirable in the radiation biological study, environmental and cosmic radiation detection, and medical radiation treatment. For these applications, the important requirements are high sensitivity, strong chemical, thermal and radiolytic stabilities, good X-ray absorption, outstanding resistance to fatigue, excellent detection performance, and mild operating conditions. The currently used commercial detectors mainly focus on radio-photoluminescence (RPL) materials, scintillators, and semiconductors, which still face severe limitations in practical application due to their inherent vice. For example, many radio-photoluminescence materials display limited luminescent stability after continuous high-dose X-ray radiation and scintillators can only record the instantaneous radiation, both of which require spectrophotometers to indirectly read the radiation signal when they are applied for X-ray detection, , while the semiconductors used as X-ray detection materials display several other disadvantages such as poor X-ray absorptivity, low detection efficiency, and harsh operating conditions. , Thus, these limitations call for the continued search for new efficient X-ray radiation detection materials.…”
Section: Introductionmentioning
confidence: 99%
“…Ionizing radiations, especially X-ray radiation from natural and artificial sources, pose a variety of potential health risks if inappropriately used, which has aroused extensive attention from our society. As such, the precise detection of X-ray radiation is highly desirable in the radiation biological study, environmental and cosmic radiation detection, and medical radiation treatment. For these applications, the important requirements are high sensitivity, strong chemical, thermal and radiolytic stabilities, good X-ray absorption, outstanding resistance to fatigue, excellent detection performance, and mild operating conditions. The currently used commercial detectors mainly focus on radio-photoluminescence (RPL) materials, scintillators, and semiconductors, which still face severe limitations in practical application due to their inherent vice. For example, many radio-photoluminescence materials display limited luminescent stability after continuous high-dose X-ray radiation and scintillators can only record the instantaneous radiation, both of which require spectrophotometers to indirectly read the radiation signal when they are applied for X-ray detection, , while the semiconductors used as X-ray detection materials display several other disadvantages such as poor X-ray absorptivity, low detection efficiency, and harsh operating conditions. , Thus, these limitations call for the continued search for new efficient X-ray radiation detection materials.…”
Section: Introductionmentioning
confidence: 99%
“…9–11 X-ray-induced photochromic (XP) compounds have been extensively studied due to their higher X-ray sensitivity than commercial silver salt-based radiographic films. 12,13 XP inorganic materials that can be realized by X-ray induction include manganite, 14 spinel, 15 tungstates, 16 oxometallates with impurities (such as LiNbO 3 :Cu), 17 Prussian blue analogs, 18 Fe II spin-crossover complexes, 19 and cobalt dioxolene. 20 Organic materials include spiropyran-based composites, 6,21 naphthalenediimide (NDI) derivatives, 22 metal complexes bearing nonionic N-heterocyclic aromatic ligands, 23 and N-substituted bipyridinium-containing compounds.…”
mentioning
confidence: 99%
“…Our studies also demonstrated the versatility of the fluorescence spectroscopy approach to assessment of the mechanism and degree of mineral oil degradation during radiative exposure. With proper calibration, this method may be used as a simple diagnostic tool for online monitoring of oil aging or for non-destructive optical diagnostics of condition/quality of various materials (or constructions) in some industrial processes as demonstrated in Nasieka et al [42] and Sobrinho et al [43]. Other methods such as colorimetric measurement, spectroscopy or viscometry are much less sensitive to chemical and especially physical changes in oil lubricants, require multiple sample preparation steps, are time consuming and/or require a larger volume of sample for such analyses.…”
Section: Resultsmentioning
confidence: 99%